Is There a Future for Non-invasive Brain Stimulation as a Therapeutic Tool? - Terranova, Carmen; Rizzo, Vincenzo; Cacciola, Alberto; Chillemi, Gaetana; Calamuneri, Alessandro; Milardi, Demetrio; Quartarone, Angelo (Frontiers in Neurology, 2019)
Several techniques and protocols of non-invasive transcranial brain stimulation (NIBS), including transcranial magnetic and electrical stimuli, have been developed in the past decades. These techniques can induce long lasting changes in cortical excitability by promoting synaptic plasticity and thus may represent a therapeutic option in neuropsychiatric disorders. On the other hand, despite these techniques have become popular, the fragility and variability of the after effects are the major challenges that non-invasive transcranial brain stimulation currently faces. Several factors may account for such a variability such as biological variations, measurement reproducibility and the neuronal state of the stimulated area. One possible strategy to reduce this variability is to monitor the neuronal state in real time using EEG and trigger TMS pulses only at pre-defined state. In addition, another strategy under study is to use the spaced application of multiple NIBS protocols within a session to improve the reliability and extend the duration of NIBS effects. Further studies, although time consuming, are required for improving the so far limited effect sizes of NIBS protocols for treatment of neurological or psychiatric disorders.